Sensibility analysis of the parameters affecting infrared thermal images for the evaluation of building pathologies - Eva Barreira (2014)
Infrared thermography is a non destructive testing technology that has been applied to detect buildings pathologies for some decades. The thermograms are affected by several parameters and it is crucial to fully understand them in order to correctly interpret the temperature readings. The infrared radiation is affected by the radiation emitted by the surface and the radiation reflected and emitted by the surroundings. Therefore there are two kinds of parameters that affect the infrared images: parameters connected to the properties of the material itself and parameters connected with the environmental conditions. In this paper we present a sensibility study of the main parameters involved with infrared thermography evaluations to detect building pathologies. To do so, some simple experiments were carried out at the Building Physics Laboratory (LFC) of the Engineering Faculty of Porto University (FEUP). The sensibility study was performed with LFC's equipment to evaluate how measurements are influenced by emissivity, reflections, absorptance and the meteorological conditions. Â(c) (2014) Trans Tech Publications, Switzerland.